The role of polyamine catabolism in anti-tumour drug response. (1st April 2003) - Casero, R.A.; Wang, Y.; Stewart, T.M.; Devereux, W.; Hacker, A.; Wang, Y.; Smith, R.; Woster, P.M.
Abstract : Interest in polyamine catabolism has increased since it has been directly associated with the cytotoxic response of multiple tumour types to exposure to specific anti-tumour polyamine analogues. Human polyamine catabolism was considered to be a two-step pathway regulated by the rate-limiting enzyme spermidine/spermine N 1 -acetyltransferase (SSAT) that provides substrate for an acetylpolyamine oxidase (APAO). Further, the super-induction of SSAT by several anti-tumour polyamine analogues has been implicated in the cytotoxic response of specific solid-tumour phenotypes to these agents. This high induction of SSAT has been correlated with cellular response to the anti-tumour polyamine analogues in several systems and considerable progress has been made in understanding the molecular mechanisms that regulate the analogue-induced expression of SSAT. A polyamine response element has been identified and the transacting transcription factors that bind and stimulate transcription of SSAT have been cloned and characterized. The link between SSAT activity and cellular toxicity is thought to be based on the production of H2 O2 by the activity of the constitutive APAO that uses the SSAT-produced acetylated polyamines. The high induction of SSAT and the subsequent activity of APAO are linked to the cytotoxic response of some tumour cell types to specific polyamine analogues. However, we have recently cloned a variably spliced human polyamine oxidase (PAOh1) that is inducible by specific polyamine analogues, efficiently uses unacetylated spermine as a substrate, and also produces toxic H2 O2 as a product. The results of studies with PAOh1 suggest that it is an additional enzyme in polyamine catabolism that has the potential to significantly contribute to polyamine homoeostasis and drug response. Most importantly, PAOh1 is induced by specific polyamine analogues in a tumour-phenotype-specific manner in cell lines representative of the major forms of solid tumours, including lung, breast, colon and prostate. The sensitivity to these anti-tumour polyamine analogues can be significantly reduced if the tumour cells are co-treated with 250 μM of the polyamine oxidase inhibitor N 1, N 4 -bis(2, 3-butadienyl)-1, 4-butanediamine (MDL 72, 527), suggesting that the H2 O2 produced by PAOh1 does in fact play a direct role in the observed cytotoxicity. These results strongly implicate PAOh1 as a new target that, in combination with SSAT, may be exploited for therapeutic advantage. The current understanding of the role and regulation of these two important polyamine catabolic enzymes are discussed.